Blunt Force May be an Effective Treatment for Ganglion Cysts. Issue 2 (July 2016) - Trivedi, Nikunj N.; Schreiber, Joseph J.; Daluiski, Aaron
Background : Ganglion cysts are the most common soft tissue tumors of the hand and wrist. There is currently no data available for the recurrence or complication rate of patients that self treat ganglion cysts by using an extrinsic force. Despite this absence of evidence, patients are still using this mode of treatment. Questions/Purposes : The purpose of the study is to evaluate the efficacy of blunt force as a treatment modality for disrupting ganglion cysts. Methods : We analyzed videos of patients attempting to disrupt their ganglion cysts of the wrist by blunt force onYoutube.com and surveyed them anonymously. Candidates were contacted through YouTube's email server and given a link to an online questionnaire. Results : Two hundred fourteen individuals were reviewed with a total of 1, 008, 913 views. Eighty three percent of videos were effective in treating the cyst. All 38 individuals that responded to the survey reported that the blunt force was effective in immediate elimination of the cyst in an average of 1.6 attempts (range 1–5). A majority ( N = 21, 55%) reported no recurrence since the initial disruption of the cyst at a follow-up of 24 months. Conclusions : YouTube.com was found to be an effective outlet to study a treatment modality that would otherwise be limited by practical considerations. The study showed that a subset of patients is utilizing blunt force trauma to successfully treat wrist ganglion cysts.